2020
DOI: 10.1098/rsos.191571
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of high conductive silver electrodes by dip-coating followed by quick sintering

Abstract: With polyol-synthesized silver nanoparticles (AgNPs) as raw materials, the silver electrodes with high conductivity were fabricated via a dip-coating method followed by sintering process, and the effects of the dip-coating and sintering process on the conductivity and surface roughness of silver electrodes were investigated in detail. The silver film with a thickness of 1.97 µm and a roughness of about 2 nm can be prepared after dip-coating at a pulling rate of 500 µm s −1 for 40 coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These results confirmed that microwave irradiation increased the size of Ag‐NPs by 2 to 10 times compared to their initial size of 20 to 30 nm, due to their fusion/sintering with each other. This fusion/sintering process has been reported in the fabrication of electrodes with Ag‐NPs, where output powers of 250 to 1000 W and irradiation times of 20 to 50 s are applied 53 . However, Ag‐Ny 200 with sizes from 9 to 22 nm were also observed, apparently, they were coated and bonded with Nylon‐6 (Figure 8e,f) but were not fused/sintered.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…These results confirmed that microwave irradiation increased the size of Ag‐NPs by 2 to 10 times compared to their initial size of 20 to 30 nm, due to their fusion/sintering with each other. This fusion/sintering process has been reported in the fabrication of electrodes with Ag‐NPs, where output powers of 250 to 1000 W and irradiation times of 20 to 50 s are applied 53 . However, Ag‐Ny 200 with sizes from 9 to 22 nm were also observed, apparently, they were coated and bonded with Nylon‐6 (Figure 8e,f) but were not fused/sintered.…”
Section: Resultssupporting
confidence: 53%
“…This fusion/sintering process has been reported in the fabrication of electrodes with Ag-NPs, where output powers of 250 to 1000 W and irradiation times of 20 to 50 s are applied. 53 However, Ag-Ny 200 with sizes from 9 to 22 nm were also observed, apparently, they were coated and bonded with Nylon-6 (Figure 8e,f) but were not fused/sintered. With these results, it is considered that the predominant process producing agglomeration and precipitation of Ag-Ny 200 is coating.…”
Section: Study Of the Hybridization Of Ag-nps With Nylon-6mentioning
confidence: 98%
“…Therefore, metal nanowires are ideal materials to replace indium tin oxide (ITO) [10,11], carbon nanotubes [12], graphene [13,14] and conductive polymers [ [15] to fabricate TCFs. Among metal nanowires, silver nanowires (AgNW) is the most promising candidate owing to excellent conductivity, relatively low cost and convenient fabrication [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, coating is a method to fabricate a film by spreading the solution on a substrate. The method is compatible for large-volume manufacture and cost-effective. And the general coating technologies for the fabrication of the Ag networks include bar-coating, spin coating, spray coating, drop casting, Meyer rod coating, etc. , After being coated on the substrate, the Ag NPs or Ag NWs form Ag networks by self-assembly quickly. However, the method always gets random networks, which will affect the sheet resistance and the transmittance of the resulting electrodes.…”
Section: Solution-based Self-assembly Methodsmentioning
confidence: 99%